Predicting Soil Organic Carbon Dynamics of Integrated Crop-Livestock System in Brazil Using the CQESTR Model - Oliveira, Janaina M.; Gollany, Hero T.; Polumsky, Robert Wayne; Madari, Beata E.; Leite, Luiz F. C.; Machado, Pedro L. O. A.; Carvalho, Márcia T. M. (Frontiers in Environmental Science, 2022)
Land degradation and reduction in productivity have resulted in losses of soil organic carbon (SOC) in agricultural areas in Brazil. Our objectives were to i) evaluate the predictive performance of CQESTR model for a tropical savannah; and ii) examine the effect of integrated management systems, including Integrated Crop-Livestock System (ICLS) scenarios on SOC stocks. Two paddocks were used in this study. In Paddock 4 (P4) the rotation was corn (Zea mays L.) and 3.5/4.5 yrs pasture (Urochloa ruziziensis), while rotations in Paddock 5 (P5) included 2.5 yrs of soybean (Glycine max L.), dryland rice (Oryza sativa L.), and corn followed by 2.5/3.5 yrs pasture (U. brizantha). Measured and CQESTR simulated values were significantly (0.0001) correlated (r = 0.94) with a mean square deviation (MSD) of 7.55, indicating that the model captured spatial-temporal dynamics of SOC. Predicted SOC increased by 18.0 and 12.04 Mg ha-1 at the rate of 0.90 and 0.60 Mg ha-1 yr-1 under current ICLS management for P4 and P5, respectively, by 2040. Both paddocks were under similar edaphic conditions; however, P4 had more time in the pasture phase with less disturbance than P5 (4.5 vs. 3.5 years pasture). Integrated Crop-Livestock System with long grass phase duration increased soil C sequestration.